Constructing porous intramolecular donor–acceptor integrated carbon nitride doped with m-aminophenol for boosting photocatalytic degradation and hydrogen evolution activity. Issue 14 (9th June 2022) - Li, Tiantian; Shi, Jingmin; Liu, Zhixue; Xie, Wei; Cui, Keyu; Hu, Bo; Che, Guangbo; Wang, Liang; Zhou, Tianyu; Liu, Chunbo
Abstract : A porous intramolecular D–A integrated carbon nitride with boosted photocatalytic activity was constructed via thermal melting followed by thermal copolymerization of m -aminophenol with urea. Abstract : Graphitic carbon nitride (CN) has been recognized as a promising photocatalyst for energy production and environmental remediation, although a high carrier recombination rate, low active site exposure and inadequate visible-light utilization prominently restrict its photocatalytic activity. Herein, a porous intramolecular D–A integrated CN for boosting photocatalytic activity under visible light was constructed via thermal melting followed by thermally induced copolymerization of m -aminophenol with urea. The optimal sample (CN30 ) possesses a porous nano-multilayer structure and superhydrophilicity, and enhanced crystallinity, specific surface area, visible light harvesting, and exciton separation and carrier migration efficiency. The hydrogen evolution rate and photodegradation rate of CN30 are 1121 μmol h −1 g −1 and 76.9% (20 mg of CN30 degrades 40 mg L −1 tetracycline), respectively, which are 2.73 and 5.3 times those of pristine CN, as well as being significantly higher than those of CNAniline and CNPhenol . DFT calculations confirm that electrons in CN30 are accumulated on the tri- s -triazine ring which serves as an electron acceptor, and the m -aminophenol unit serves as an electron donor to promote faster electron transfer to the CN skeleton. ESR and free radical capture experiments confirm that 1 O2 and ˙O2 − are the dominant active species. And LC-MS clarifies the intermediates and pathways in the process of TC photodegradation. This research provides a new reference for boosting the activity of integrated CN photocatalytic materials for solar-to-chemical energy conversion.